The Pembentukan Peer Counselor Sebagai Upaya Social Support dan Upaya Preventif Terhadap Isu-Isu Kesehatan Mental pada Mahasiswa di Universitas Kristen Duta Wacana - Setyaningtyas, Angelina Dyah Arum; Anggraeni, Dewi Soerna; Sandiasih, Komang Mahadewi (Universitas Dinamika, 2025)
Mental health issues among university students have become an increasingly urgent concern, including at Duta Wacana Christian University (UKDW) Yogyakarta, which currently has around 3,500 active students. This community service program aimed to enhance social support and promote preventive efforts against mental health problems through the establishment of peer counselors within the campus environment. The program was implemented from January to March 2024, with student participants from the Counseling Division of LPKKSK UKDW as the main target group. The implementation was carried out in several stages: participant selection, basic counseling skills training conducted over three sessions, roleplay practice, and a final stage involving the socialization of the counseling service flow and referral system. The results showed a significant increase in participants' knowledge and counseling skills, as evidenced by the paired samples t-test, which yielded a p-value of 0.016. The rise in average scores from pre-test to post-test, along with reduced score variance among participants, reflects the uniform effectiveness of the training provided. The implication of this program highlights that involving peer counselors can serve as an effective solution to the limited availability of professional counselors on campus. Moreover, it strengthens a community-based support ecosystem, empowers students as agents of change, and offers a scalable model for psychosocial intervention that could be replicated in other higher education settings.